An albumin-based tumor-targeted oxaliplatin prodrug with distinctly improved anticancer activity in vivo. Issue 3 (15th December 2016) - Mayr, Josef; Heffeter, Petra; Groza, Diana; Galvez, Luis; Koellensperger, Gunda; Roller, Alexander; Alte, Beatrix; Haider, Melanie; Berger, Walter; Kowol, Christian R.; Keppler, Bernhard K.
Abstract : An oxaliplatin-based platinum(iv ) drug which specifically binds to albumin after i.v. application led to several complete responses in tumor-bearing mice. Abstract : The design of targeted platinum(iv ) prodrugs is a very promising approach to enhance the low selectivity of platinum(ii ) drugs towards cancerous tissue in order to reduce the impact on healthy tissue and, consequently, the often severe side-effects. Herein, we report a set of mono-functionalized cis- and oxaliplatin-based platinum(iv ) complexes bearing a maleimide moiety, which allows selective binding to serum albumin in the bloodstream. This leads not only to a prolonged plasma half-life by avoidance of fast renal clearance, but also to preferential accumulation of the drug in the tumor tissue due to the EPR-effect. Additionally, analogous succinimide-functionalized derivatives were prepared to verify the influence of the maleimide moiety. First experiments showed that all the maleimide compounds are stable and also possess good albumin-binding properties in whole serum. Further analytical studies on in vivo samples proved the highly increased plasma half-life, as well as tumor accumulation of the maleimide-functionalized substances. In vivo antitumor experiments with CT-26-bearing mice showed that, in contrast to the cisplatin derivatives, the oxaliplatin-based complexes had exceptionally better activity than the free drug resulting in the cure of the majority of treated mice. Subsequent analysis suggested that a distinctly faster reduction as well as reduced tumor accumulation of the cisplatin derivative might explain the worse performance compared to the oxaliplatin(iv ) complexes. Taken together, a novel lead platinum(iv ) complex with outstanding antitumor activity is presented, which will now be further developed towards clinical phase I trials.